BANGUNAN MODULAR LOW-RISE UNTUK RUMAH TINGGAL DI KAWASAN KABUPATEN TANGERANG - Budi Setiawan; Richardus Eko Indrajit; Erick Dazki (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2022)
Population development must be balanced with the fulfillment of housing needs. It is increasingly difficult for people to reach house prices in an area suitable for many family members in big cities. A successful construction project is measured by three factors: the correct cost, excellent quality, and the right time. The project should be completed at a cost that is not more than the budget plan; at the time of handover, it must be checked whether the project is following the specified specifications and quality; in addition, the project must also be completed no later than the agreed time. Due to these three benchmarks, it is recommended that the fulfillment of residential needs using a modular system is recommended. This research will answer (1) How is the need for residential houses in the Big City by determining the sample in Tangerang Regency? (2) How is the effectiveness of using a modular system for residential houses if the coding process is carried out during the construction phase? The results showed (1) that the need for housing for two people and three people in the Tangerang Regency area is significant; therefore, a low-cost and efficient development process is needed. The modular system is deemed suitable for Tangerang by looking at these conditions. (2) The coding of the modular system makes the installation faster and with waste/material residue to be more cost-effective. In addition, the modular system for residential houses has been widely developed in the field.